The promotion of mental health and the prevention of mental health problems in child and adolescent - Sun Mi Cho; Yun Mi Shin (Korean Journal of Pediatrics, 2013)
Improving mental health and reducing the burden of mental illness are complementary strategies which, along with the treatment and rehabilitation of people with mental disorders, significantly improve population health and well-being. A Institute of Medicine report describes a range of interventions for mental disorders that included treatment and maintenance, reserving the term "prevention" for efforts that occur before onset of a diagnosable disorder. Mental health problems affect 10-20% of children and adolescents worldwide. Despite their relevance as a leading cause of health-related disability and their long lasting consequences, the mental health needs of children and adolescents are neglected. Early intervention can help reduce the significant impacts that children and adolescents with serious mental health problems may experience. Screening is the first step in early intervention, recognizing emotional and behavioral problems and providing help at an early stage. It is essential to implement early intervention in a sensitive and ethical manner to avoid any of the negative outcomes.